UJI SENSITIVITAS ISOLAT Aeromonas salmonicida DARI IKAN NILA (Oreochromis niloticus) TERHADAP BEBERAPA ANTIBIOTIK - , MUHAMMAD TAUFIQ F; , Prof. drh. Kurniasih, MVSc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Aeromonas salmonicida is a Gram-negative bacteria that are pathogenic to fresh water and sea water fish, can cause furunculosis and mortality, impact on economic losses. This study aimed to determine the sensitivity of the isolates of Aeromonas salmonicida isolated from nile tilapia (Oreochromis niloticus) to some of antibiotics. Three isolates of Aeromonas salmonicida tested for its sensitivity level using the Kirby-Bauer disk diffusion method on Mueller Hinton Agar as the media. Ampicillin disk, doxycycline disk, eryhtromycin disk, enrofloxacin disk, and gentamicin disk, using tweezers, positioned on the surface of bacterial culture, and then incubated for 24 hours at 28oC. The diameter of zones of inhibition around the antibiotic disk that formed being compared to the Kirby-Bauer stanbard. The result show that three isolates of Aeromonas salmonicida sensitive to ampicillin (33,3%), doxycycline (33,3%), enrofloxacin (100%), and gentamicin (100%), intermediet to doxycycline (66,7%) and erythromycin (100%), and resistant to ampicillin (67,7%). Based on the zones of inhibition were formed, enrofloxacin and gentamicin are effective for treating infections caused by Aeromonas salmonicida in nile tilapia.